Infecciones bacterianas, micóticas y virales en muestras cervicales de estudiantes de la Facultad de Ciencias de la Salud. - Hernández Chacha, Andrés Santiago (2024)
Vulvovaginal infections frequently cause consultation in primary care, presenting a wide range of clinical manifestations and etiologies. These infections are especially problematic in women of childbearing age and with an active sexual life since they can generate inflammatory reactions and defects in the genital epithelium of significant clinical relevance. This study aimed to assess the prevalence of bacterial, fungal, and viral infections in cervical samples of female students of the Faculty of Health Sciences of the National University of Chimborazo during 2023 - 2S. The research had a mixed approach design, combining quantitative and qualitative analysis with an exploratory-descriptive and cross-sectional cohort design. The study population was 1,939 students, and 124 samples were analyzed. The results indicated that 55.6% were between 16 and 18 years of age at the beginning of their sexual life, and 32.3% had no infection. However, 56.5% of the samples revealed infection by Gardnerella vaginalis, 6.5% by Candida albicans, and 4.8% showed mixed infection. Regarding cytology, 75.8% showed no alterations, while 13.7% presented ASC-US, 8.1% L-SIL, 1.6% H-SIL and 0.8% ASC-H. It was concluded that risk factors such as early sexual debut, multiple sexual partners, and the use of contraceptives were associated with increased infections, underscoring the need for better hygiene and prevention strategies to ensure sexual and reproductive health in this population.